PENINGKATAN KREATIVITAS SISWA MELALUI STRATEGI PEMBELAJARAN BERBASIS PROYEK DI MADRASAH IBTIDAIYAH - Hermansyah, David; Ali, Mustapa; Aqodiah, Aqodiah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2025)
This study aims to evaluate the implementation of Project-Based Learning (PBL) strategies in enhancing students' creativity at Madrasah Ibtidaiyah. Utilizing a Systematic Literature Review (SLR) method, the research analyzes literature indexed in Scopus, DOAJ, and Google Scholar from 2017 to 2024. The findings reveal that PBL holds significant potential in increasing student engagement, creativity, and problem-solving skills. However, its implementation in Madrasah Ibtidaiyah faces several challenges, including limited resources, time constraints, and insufficient teacher training. Additionally, logistical issues such as large class sizes, inadequate facilities, and difficulties in fostering team collaboration among students pose substantial barriers. The role of teachers as facilitators is crucial in ensuring the success of PBL, yet it requires support through continuous training, curriculum alignment, and effective time management. This study recommends enhancing teacher capacity and developing infrastructure to optimize PBL practices for fostering student creativity.